Discovery of potent, selective, and orally bioavailable inhibitors of interleukin-1 receptor-associate kinase-4. Issue 23 (1st December 2015) - Wang, Zhulun; Sun, Daqing; Johnstone, Sheree; Cao, Zhaodan; Gao, Xiong; Jaen, Juan C.; Liu, Jingqian; Lively, Sarah; Miao, Shichang; Sudom, Athena; Tomooka, Craig; Walker, Nigel P.C.; et al.
Graphical abstract: Abstract: In this Letter, we report the continued optimization of the N -acyl-2-aminobenzimidazole series, focusing in particular on the N -alkyl substituent and 5-position of the benzimidazole based on the binding mode and the early SAR. These efforts led to the discovery of16, a highly potent, selective, and orally bioavailable inhibitor of IRAK-4.